2004
DOI: 10.1099/jmm.0.05515-0
|View full text |Cite
|
Sign up to set email alerts
|

Sequence variation and conservation in virulence-related genes of Bordetella pertussis isolates from the UK

Abstract: To determine the value of gene markers for surveillance and to assess the genetic stability of potential acellular pertussis vaccine components, the sequence variation in ten virulence-related genes of Bordetella pertussis was investigated in strains isolated in the UK between 1920 and 2002. These genes encode: pertactin (prnA); pertussis toxin subunits S1 (ptxA) and S3 (ptxC); tracheal colonization factor (tcfA); bordetella autotransporter protein C (bapC); bordetella resistance to killing protein (brkA); fim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
72
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(80 citation statements)
references
References 32 publications
6
72
0
2
Order By: Relevance
“…Previous studies have revealed very little polymorphism in B. pertussis surface proteins. (5,18,21,22,28,38). We focused on genes for proteins incorporated in the ACVs and which were shown to be polymorphic in previous studies: ptxC, ptxA, and prn.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed very little polymorphism in B. pertussis surface proteins. (5,18,21,22,28,38). We focused on genes for proteins incorporated in the ACVs and which were shown to be polymorphic in previous studies: ptxC, ptxA, and prn.…”
Section: Discussionmentioning
confidence: 99%
“…The choice of covariates and end points are highly decisive for whether differences in pathogenicity between B. pertussis isolates can be demonstrated or not, and should be made carefully (Table 2). The most commonly used B. pertussis strains in animal models of infection, 18323, Wellcome 28 and Tohama I, are laboratory subcultured and attenuated strains, and hence genetically different from clinical isolates [37,114,119]. Since differences in genome sequences may affect the pathogenicity of B. pertussis in animals and humans, these laboratory strains are not representative for current B. pertussis strains.…”
Section: Infection Modelsmentioning
confidence: 99%
“…However, the two key factors held responsible for the pertussis resurgence in vaccinated populations are, on the one hand, the appearance of new B. pertussis strain variants, and on the other hand, the gradual loss of vaccine-induced protective immunity in vaccinees, in an era of less circulation and natural boosting (Figure 1). The relative impact of these factors in the resurgence of pertussis is under investigation and may differ between subpopulations and countries [35][36][37][38].…”
Section: Resurgence Of Pertussismentioning
confidence: 99%
“…B. pertussis expresses two serologically distinct fimbriae composed of either Fim2 or Fim3 subunits (22.5 and 22.0 kDa, respectively). Subtypes of Fim2 (fim2-1 and fim2-2) and Fim3 (fim3-1, fim3-2 and fim3-3) have also been described (Packard et al, 2004;Tsang et al, 2004). Both Fim2 and Fim3 subunits are assembled in a coil to produce long filaments on the surface of the bacteria (Heck et al, 1996).…”
Section: Introductionmentioning
confidence: 99%